2018
DOI: 10.1108/wwop-02-2018-0007
|View full text |Cite
|
Sign up to set email alerts
|

Articulating the unique competencies of admiral nurse practice

Abstract: Purpose The purpose of this paper is to describe the process of developing a contemporary competency framework for admiral nurses in dementia care. Design/methodology/approach Information and evidence was gathered from research and policy literature regarding competencies to deliver advanced practice within dementia care. An online survey completed by 75 admiral nurses with follow-up interviews clarified current practice across the range of service contexts in which they work. A focus group (FG) of people li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 3 publications
0
21
0
Order By: Relevance
“…In observation of practise, there were no studies that utilised observation of interactions between clinicians and patients. Authors reported including service users, such as patient representatives and carers, in the development process to ensure that the resulting competency framework encompassed the needs of patients, families and carers ( 7 , 9 , 57 ). Framed as “experts by experience,” Carter et al note that a focus group with service users helped to shape the content of the admiral nurse competency framework, based on their unique experience and expectations of care ( 57 ), though the sample was small ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In observation of practise, there were no studies that utilised observation of interactions between clinicians and patients. Authors reported including service users, such as patient representatives and carers, in the development process to ensure that the resulting competency framework encompassed the needs of patients, families and carers ( 7 , 9 , 57 ). Framed as “experts by experience,” Carter et al note that a focus group with service users helped to shape the content of the admiral nurse competency framework, based on their unique experience and expectations of care ( 57 ), though the sample was small ( n = 5).…”
Section: Resultsmentioning
confidence: 99%
“…Authors reported including service users, such as patient representatives and carers, in the development process to ensure that the resulting competency framework encompassed the needs of patients, families and carers ( 7 , 9 , 57 ). Framed as “experts by experience,” Carter et al note that a focus group with service users helped to shape the content of the admiral nurse competency framework, based on their unique experience and expectations of care ( 57 ), though the sample was small ( n = 5). Cashin et al ( 4 ) state that partnering with service users is fundamental to the development of standards for practise for registered nurses providing person-centred health care.…”
Section: Resultsmentioning
confidence: 99%
“…El-Haddad et al ( 11 ) demonstrated how patient involvement can both identify areas overlooked by clinicians and also complement their perspective. Other collaborative approaches included involvement in multiple stages of the development process such as competency statement generation and consensus techniques [example: ( 10 , 27 , 36 , 40 , 41 , 43 , 50 , 57 )] or inclusion in project references groups overseeing the progress of the whole development process [example: ( 10 , 23 , 25 , 36 , 37 )]. There was a lack of critical evaluation of these collaborative approaches making it difficult to determine the most effective way to use these methods in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Admiral Nurses are highly skilled practitioners who work at an advanced level of practice to provide specialist care and support to families affected by dementia, and they tend to manage the more complex of cases (Carter et al, 2018;Gridley et al, 2019). Admiral Nurses work within a range of different host organisations and settings, including hospitals, community teams, hospices, care homes and the charitable sector, and are supported in their ongoing professional development by Dementia UK.…”
Section: Box 1: the Rbl Admiral Nurse Servicementioning
confidence: 99%